Relating products and taylor series

Calculus Level 5

m = 1 [ 1 2 exp ( n = 1 m ( 1 ) n 1 n ) ] = exp ( 1 ) 2 × exp ( 1 1 2 ) 2 × exp ( 1 1 2 + 1 3 ) 2 × exp ( 1 1 2 + 1 3 1 4 ) 2 × \prod_{m=1}^\infty \left [ \dfrac12 \exp \left(\sum_{n=1}^m \dfrac{ (-1)^{n-1}}n \right) \right ] = \dfrac{\exp(1)}2 \times \dfrac{\exp\left (1- \frac12\right)}2 \times\dfrac{\exp\left (1- \frac12+ \frac13\right)}2 \times\dfrac{\exp\left (1- \frac12+ \frac13- \frac14\right)}2 \times \cdots

Evaluate the infinite product above, where exp ( x ) = e x \exp(x) = e^x .

If your answer can be expressed as r × e s , r \times e^{s}, where r r and s s are rational numbers, give your answer as r + s r+s .


Bonus: Give a closed form of m = 1 [ 1 1 x exp ( n = 1 m x n n ) ] \displaystyle \prod_{m=1}^\infty \left [ \dfrac1{1-x} \exp \left(-\sum_{n=1}^m \dfrac{x^{n}}n \right) \right ] for 1 x < 1 -1\leq x < 1 .


The answer is 1.5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Sep 16, 2017

Since m = 1 2 M [ 1 2 exp ( n = 1 m ( 1 ) n 1 n ) ] = 1 2 2 M exp [ m = 1 2 M n = 1 m ( 1 ) n 1 n ] = 1 2 2 M exp [ n = 1 2 M ( 1 ) n 1 ( 2 M + 1 n ) n ] = 1 2 2 M exp [ ( 2 M + 1 ) n = 1 2 M ( 1 ) n 1 n ] = exp [ ( 2 M + 1 ) ( H 2 M H M ) 2 M ln 2 ] \begin{aligned} \prod_{m=1}^{2M}\left[ \frac12 \exp\left(\sum_{n=1}^m \frac{(-1)^{n-1}}{n}\right)\right] & = \; \frac{1}{2^{2M}}\exp\left[\sum_{m=1}^{2M}\sum_{n=1}^m \frac{(-1)^{n-1}}{n}\right] \; = \; \frac{1}{2^{2M}} \exp\left[\sum_{n=1}^{2M}\frac{(-1)^{n-1}(2M+1-n)}{n}\right] \\ & = \; \frac{1}{2^{2M}}\exp\left[(2M+1)\sum_{n=1}^{2M}\frac{(-1)^{n-1}}{n}\right] \; = \; \exp\big[(2M+1)(H_{2M} - H_M) - 2M\ln2\big] \end{aligned} Since H N = ln N + γ + 1 2 N + O ( N 2 ) N H_N \; = \; \ln N + \gamma + \frac{1}{2N} + O\big(N^{-2}\big) \hspace{2cm} N \to \infty we see that ( 2 M + 1 ) ( H 2 M H M ) 2 M ln 2 = ln 2 2 M + 1 4 M + O ( N 1 ) N (2M+1)(H_{2M} - H_M) - 2M\ln 2 \; = \; \ln2 - \frac{2M+1}{4M} + O\big(N^{-1}\big) \hspace{2cm} N \to \infty and hence, letting M M \to \infty , m = 1 [ 1 2 exp ( n = 1 m ( 1 ) n 1 n ) ] = exp [ ln 2 1 2 ] = 2 e 1 2 \prod_{m=1}^{\infty}\left[ \frac12 \exp\left(\sum_{n=1}^m \frac{(-1)^{n-1}}{n}\right)\right] \; = \; \exp\big[\ln2 - \tfrac12\big] \; = \; 2e^{-\frac12} making the answer 2 1 2 = 3 2 2 - \tfrac12 = \boxed{\tfrac32} .

The result for 1 < x < 1 -1 < x < 1 is perhaps a little easier. m = 1 M [ 1 1 x exp ( n = 1 m x n n ) ] = 1 ( 1 x ) M exp [ m = 1 M n = 1 m x n n ] = 1 ( 1 x ) M exp [ n = 1 M ( M + 1 n ) x n n ] = 1 ( 1 x ) M exp [ x ( 1 x M ) 1 x ( M + 1 ) n = 1 M x n n ] = exp [ x ( 1 x M ) 1 x ( M + 1 ) n = 1 M x n n M ln ( 1 x ) ] = exp [ x ( 1 x M ) 1 x n = 1 M x n n + M n = M + 1 x n n ] \begin{aligned} \prod_{m=1}^M \left[\frac{1}{1-x}\exp\left(-\sum_{n=1}^m \frac{x^n}{n}\right)\right] & = \; \frac{1}{(1-x)^M}\exp\left[-\sum_{m=1}^M\sum_{n=1}^m \frac{x^n}{n}\right] \; = \; \frac{1}{(1-x)^M}\exp\left[-\sum_{n=1}^M \frac{(M+1-n)x^n}{n} \right] \\ & = \; \frac{1}{(1-x)^M}\exp\left[\frac{x(1-x^M)}{1-x} - (M+1)\sum_{n=1}^M \frac{x^n}{n}\right] \; = \; \exp\left[ \frac{x(1-x^M)}{1-x} - (M+1)\sum_{n=1}^M \frac{x^n}{n} - M\ln(1-x)\right] \\ & = \; \exp\left[\frac{x(1-x^M)}{1-x} - \sum_{n=1}^M \frac{x^n}{n} + M\sum_{n=M+1}^\infty \frac{x^n}{n}\right] \end{aligned} Since M m = M + 1 x n n M M + 1 n = M + 1 x n x M + 1 1 x \left| M\sum_{m=M+1}^\infty \frac{x^n}{n}\right| \; \le \; \frac{M}{M+1}\sum_{n=M+1}^\infty |x|^n \; \le \; \frac{|x|^{M+1}}{1-|x|} we deduce that lim M ( x ( 1 x M ) 1 x n = 1 M x n n + M n = M + 1 x n n ) = x 1 x + ln ( 1 x ) \lim_{M \to \infty} \left(\frac{x(1-x^M)}{1-x} - \sum_{n=1}^M \frac{x^n}{n} + M\sum_{n=M+1}^\infty \frac{x^n}{n}\right) \; = \; \frac{x}{1-x} + \ln(1-x) and hence m = 1 [ 1 1 x exp ( n = 1 m x n n ) ] = ( 1 x ) exp [ x 1 x ] x < 1 \prod_{m=1}^\infty \left[\frac{1}{1-x}\exp\left(-\sum_{n=1}^m \frac{x^n}{n}\right)\right] \; = \; (1-x)\exp\left[\frac{x}{1-x}\right] \hspace{2cm} |x| < 1

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...